1998
DOI: 10.1159/000010028
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Change in Uterine Activity to Blood Loss in theThird Stage of Labour

Abstract: In 47 women, the change in the uterine activity after the administration of a uterotonic agent was correlated with the amount of blood loss during the same period of time. Uterine activity was measured by a Gaeltec® catheter-tipped pressure transducer inserted transcervically within 5 min of delivery of the placenta. A uterotonic agent (either intravenous syntocinon, intramuscular syntometrine or oral misoprostol) was given after the insertion of the intrauterine pressure catheter and pressure recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…The mechanical constriction of the blood vessels due to the uterine muscle contraction and retraction and by clots sealing off the raw surface in the placental bed usually stops uterine bleeding at the site of placental separation. 18 Uterine contractions are promoted by the pituitary hormone oxytocin, whose release is stimulated by the stretching of the cervix and vaginal canal during birth and by nipple stimulation during lactation. 19 Coagulation factors in the maternal blood contribute to the formation of clots that also stem the blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical constriction of the blood vessels due to the uterine muscle contraction and retraction and by clots sealing off the raw surface in the placental bed usually stops uterine bleeding at the site of placental separation. 18 Uterine contractions are promoted by the pituitary hormone oxytocin, whose release is stimulated by the stretching of the cervix and vaginal canal during birth and by nipple stimulation during lactation. 19 Coagulation factors in the maternal blood contribute to the formation of clots that also stem the blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…The research team hypothesized the inconsistency was the result of biologic variations. Using the same catheter‐tipped pressure transducer method, Choo et al (8) studied a small group of 47 women and found that increased uterine activity immediately after placental expulsion tended to correlate with a decrease in total blood loss; however, they recognized the limits of the small study and recommended larger studies to explore the strength of relationship as well as other potential influences that could impact the results. In general, these studies supported conventional wisdom that early uterine activity with early expulsion of the placenta tended to result in less overall blood loss.…”
Section: Blood Loss During Third Stagementioning
confidence: 99%
“…Other studies have used IUPCs following the expulsion of the placenta 7–10 . No cases were described in these studies that did not record contractions.…”
Section: Commentmentioning
confidence: 99%
“…No cases were described in these studies that did not record contractions. The description of the insertion was the same as in this study 7–10 . The uterine activity was reported in a summative manner rather than providing contraction frequency and intensity, because sometimes uterine contractions following placental expulsion would be tetanic or hypertonic, such that return of the contraction curve to the baseline took several minutes 10 .…”
Section: Commentmentioning
confidence: 99%